Treatment planning of intracranial lesions with VHEE: comparing conventional and FLASH irradiation potential with state-of-the-art photon and proton radiotherapy - Muscato, A.; Arsini, L.; Battistoni, G.; Campana, L.; Carlotti, D.; De Felice, F.; De Gregorio, A.; De Simoni, M.; Di Felice, C.; Dong, Y.; Franciosini, G.; Marafini, M.; et al. (Frontiers in Physics, 2023)
The treatment of deep seated tumours with electrons of very high energies (VHEE, MeV) has already been explored in the past suggesting that a dosimetric coverage comparable with state-of-the-art proton (PT) or photon (RT) radiotherapy could be achieved with a large (> 10) number of fields and high electrons energy. The technical and economical challenges posed by 1 A. Muscato et al.the deployment of such beams in treatment centres, together with the expected small therapeutic gain, prevented the development of such technique. This scenario could radically change in light of the recent developments occurred in the compact, high gradient, electrons acceleration technology and, additionally, of the experimental evidence of organs at risk sparing achieved in ultra high dose rate irradiation, also referred to as FLASH. Electrons with the energy required to treat intracranial lesions could be provided, at dose rates compatible with what is needed to trigger the FLASH effect, by accelerators that are a few meters long, and the organs sparing could be exploited to significantly simplify the irradiation geometry, decreasing the number of fields needed to treat a patient.In this paper the case of two patients affected respectively by a chordoma and a meningioma, treated with protons in Trento (IT) is presented. The proton plans have been compared with VHEE plans and X-Ray intensity modulated (IMRT) plans. The VHEE plans were first evaluated in terms of physical dose distribution, and then assuming that the FLASH regimen can be achieved. VHEE beams demonstrated their potential in obtaining plans that have comparable tumour coverage and organs at risk sparing when bench-marked against current state-of-the-art IMRT and PT.These results were obtained with a number of explored fields that was in the range between 3 and 7, consistently with what is routinely done in IMRT and PT conventional irradiations. The FLASH regimen, in all cases, showed its potential in reducing the damage in the organs placed nearby the target volume allowing, especially in the chordoma case where the irradiation geometry is more challenging, a better tumour coverage with respect to the conventional one.